Recent Developments in the Deoxyfluorination of Alcohols and Phenols: New Reagents, Mechanistic Insights, and Applications - Hu, Wen-Li; Hu, Xiang-Guo; Hunter, Luke (Synthesis, 2017)
This short review describes the development of new reagents and methods for the deoxyfluorination of phenols and alcohols during the period of 2011 to 2017. Important advances in the mechanistic understanding of these processes are discussed. The continuing importance of deoxyfluorination chemistry for the synthesis of valuable target molecules is highlighted through case studies including examples of 18F-radiosynthesis and the preparation of exotic multifluorinated compounds.1 Introduction2 New Deoxyfluorination Reagents3 Novel Applications of ‘Legacy’ Deoxyfluorinating Reagents4 Conclusions and Future Directions
Keywords: deoxyfluorination; PhenoFluor; PyFluor; CpFluor; multi-vicinal fluoroalkanes